Prevalence, intensity and risk factors of soil-transmitted helminthiasis after five effective rounds of preventive chemotherapy across three implementation units in Ondo State, Nigeria. - Hammed O Mogaji; Francisca O Olamiju; Fajana Oyinlola; Ijeoma Achu; Oladunni N Adekunle; Lydia E Udofia; Ekaette G Edelduok; Clement A Yaro; Olanike O Oladipupo; Alice Y Kehinde; Fatai Oyediran; Moses Aderogba; et al. (PLoS Neglected Tropical Diseases)
Background Routine epidemiological data are essential for monitoring the effectiveness of preventive chemotherapy (PC), optimizing resource allocation, and addressing the evolving needs in the elimination of soil-transmitted helminthiasis (STH). This study assesses the prevalence, intensity, and associated risk factors of STH following five rounds of albendazole-based PC in three implementation units (IUs) in Ondo State, Nigeria. Methodology Fresh stool samples were collected from 2,093 children aged 5-14 years across 45 systematically selected schools in three IUs: Ese-Odo, Irele, and Ile-Oluji. The samples were analyzed using the Kato-Katz technique. Additionally, standardized questionnaires were administered to gather data on demographics and access to water, sanitation, and hygiene (WASH) resources. Data analysis was conducted using R software version 4.3.2, with a 95% confidence interval. Principal findings/conclusions The parasitological data indicated a significant decline in the aggregated prevalence of STH across the three IUs. In Ese-Odo, the prevalence decreased to 25.8% (95% CI: 23.0-29.0) from 39% at baseline (d = -34%, p = 0.00). In Irele, prevalence dropped to 9.7% (95% CI: 7.6-12.0) from 51.3% at baseline (d = -81%, p = 0.00), and in Ile-Oluji, prevalence was reduced to 6.4% (95% CI: 4.6-8.7) from 23% at baseline (d = -72.2%, p = 0.00). The most prevalent STH species was Ascaris lumbricoides, with infection rates of 25.5%, 9.4%, and 6.4% in Ese-Odo, Irele, and Ile-Oluji, respectively, followed by Trichuris trichiura in Ese-Odo (2.7%) and Irele (0.4%), while hookworm infections were detected only in Irele (0.7%). The majority of infections were of low intensity in Ese-Odo (91.0%), Irele (96.8%), and Ile-Oluji (100%). Access to improved sanitation (17.7%, 54.9%, and 58.2%), improved water sources (24.5%, 66.1%, and 69.8%), and handwashing facilities (9.0%, 39.6%, and 25.4%) was suboptimal and significantly varied across Ese-Odo, Irele, and Ile-Oluji, respectively (p < 0.05). Open defecation rates were high in Ese-Odo (54.2%), Irele (36.3%), and Ile-Oluji (34.3%). In Ese-Odo, significant risk factors for STH infection included the use of hand-pump boreholes (AOR: 2.44, 95% CI: 1.23-4.88, p = 0.01), unprotected dug wells (AOR: 3.25, 95% CI: 0.96-11.36, p = 0.06), ventilated improved pit latrines (AOR: 3.95, 95% CI: 1.13-16.1, p = 0.04), pit latrines without a slab (AOR: 2.19, 95% CI: 1.27-3.8, p = 0.01), and failure to use soap after defecation, both when soap was available (AOR: 12.09, 95% CI: 1.86-112.97, p = 0.01) and when soap was unavailable (AOR: 8.19, 95% CI: 1.73-76.65, p = 0.04). In Irele, access to protected dug wells was marginally significant (AOR: 1.79, 95% CI: 0.96-3.21, p = 0.06), while in Ile-Oluji, access to river water emerged as a significant risk factor (AOR: 7.97, 95% CI: 1.81-58.58, p = 0.02). The use of rainwater was found to be protective across all three IUs. These findings demonstrate significant progress in reducing STH prevalence across the three IUs following PC interventions. However, the data underscores the need for enhanced efforts to improve access to and use of WASH facilities to achieve STH elimination.